AWE-06 Outcomes of hemospray use in tumour related upper gastrointestinal bleeds: Outcomes from the hemospray registry. (June 2019) - Hussein, Mohamed; Alzoubaidi, Durayd; Fraile, Miguel; Fernandez-sordo, Jacobo Ortiz; Ragunath, Krish; Rusu, Radu; Dunn, Jason; Rey, Johannes; Gulati, Shraddha; Hayee, Bu'Hussain; Dixon, Selena; Moreea, Sulleman; et al.
Abstract : Introduction: Patients with tumour related upper gastrointestinal bleeds (UGIBs) are challenging to treat. Hemospray (Cook Medical, North Carolina, USA) is a novel haemostatic powder for GI bleeding. The primary aim was to look at outcomes of UGIBs secondary to tumours who had Hemospray therapy in 13 centres. Methods: Data was prospectively collected on the use of hemospray from specialist centres in the UK, France, Germany (Jan'16-September'18). Hemospray was used for UGIBs secondary to tumours as a monotherapy, dual-therapy with standard haemostatic techniques or rescue therapy. Haemostasis was defined as the cessation of bleeding within 5 minutes of the application of hemospray. Results: 75 patients with tumoural UGIBs were recruited (51 males, 24 females, 22/75 (29%) oesophageal, 49/75 (65%) gastric, 4/75 (5%) doudenal). The median rockall score was 8 (IQR, 7–9). Immediate haemostasis was achieved in 73/75 (97%) of patients, 7/65 (11%) had a rebleed, 12/65 (18%) died within 30 days (all-cause mortality). Based on the baseline average total rockall score, the expected rebleed rate is 25–40%, and expected mortality rate was 40–45% in our cohort. 100% immediate haemostasis was achieved in duodenal and gastric tumours, and 91% in oesophageal tumours. Outcomes with mono/combination therapy and rescue therapy (table 1 ) Conclusions: Hemospray is effective for achieving immediate haemostasis in UGIBs secondary to upper GI tumours, which are considered difficult to treat. When considering average rockall score the rebleed and mortality rate is better than predicted rates. Haemostasis is achieved in the majority allowing for patient stabilization and providing time for surgery/radiotherapy.